2003
DOI: 10.1063/1.1544078
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity calibration for hot wire based dc scanning thermal microscopy

Abstract: Thermal conductivity characterization with nanoscale spatial resolution can be performed by contact probe techniques only. The technique based on a hot anemometer wire probe mounted in an atomic force microscope is now a standard setup. However, no rigorous calibration procedure is provided so far in basic dc mode. While in contact with the sample surface, the electrical current I injected into the probe is controlled so that electrical resistance or the wire temperature is maintained by the Joule effect. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 3 publications
1
66
0
Order By: Relevance
“…In those conditions, the range of radius values is 1.5-3.3μm (90%) and 4 -5.4μm (50%). A value of 1μm for b was obtained in previous works [7] from experimental data when the tip temperature is higher than 100°C. In those conditions, the meniscus disappears and air conduction becomes predominant.…”
Section: Conduction Through Airmentioning
confidence: 99%
See 2 more Smart Citations
“…In those conditions, the range of radius values is 1.5-3.3μm (90%) and 4 -5.4μm (50%). A value of 1μm for b was obtained in previous works [7] from experimental data when the tip temperature is higher than 100°C. In those conditions, the meniscus disappears and air conduction becomes predominant.…”
Section: Conduction Through Airmentioning
confidence: 99%
“…The temperatures at both ends are set to the ambient because the silver is assimilated to a heat sink. The detailed solving of the thermal problem is proposed in references [7,9]. The expression of the probe-sample conductance G eq including the contact G C and the sample G S contributions writes:…”
Section: The Sthm Based On a Hot Tipmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat flux q on the top of sample surface due to convection is governed by boundary convection: estimate a circular contact surface with a 80 nm radius and a concentric circular water meniscus surface with an outside radius of 306 nm. As for Lefèvre et al [17][18][19], they have suggested contact radii values ranging from 200 nm to 1 µm depending on temperature and probe geometry.…”
Section: Contact Area Between the Probe And The Samplementioning
confidence: 99%
“…By scanning a heated tip across the sample surface a spatial map of the thermal properties of the sample may be mapped out as localized heat transfer between the tip and sample surface changes the tip temperature. Many theoretical and instrumental studies have been devoted to the measurement of temperature and conductivity [4][5][6][7][8][9][10][11][12][13]. However, the results obtained depend strongly on the nature of the tip-surface contact, which is poorly defined [3,10].…”
Section: Introductionmentioning
confidence: 99%